PENGARUH LAYANAN BRILINK TERHADAP INKLUSI KEUANGAN DI KABUPATEN SOPPENG - Nurul Fahmi Sultan; Rezky Ramadhani; Eva Musdalifa; Rica Yulianti Lukman (Journal AK-99, 2026)
This study aims to measure the role of BRILink services as an instrument in increasing access and utilization of financial services in Lalabata District, Soppeng Regency. The background of this study is based on the importance of financial inclusion in driving economic growth, reducing inequality, and improving community welfare, especially in areas with limited access to formal financial institutions. The presence of BRILink agents is expected to bridge this gap by providing more accessible, fast, and efficient financial services for the community. This study uses a quantitative method to analyze the effect of BRILink services on increasing financial inclusion. The data used are primary data collected through the distribution of Likert-based questionnaires to respondents who are active users of BRILink services in Lalabata District. The number of samples in this study was 75 respondents determined using the Slovin formula. The data analysis technique used was simple linear regression with the help of the SPSS application to test the relationship between BRILink service variables and the level of community financial inclusion. The results show that BRILink services have a positive and significant influence on increasing financial inclusion. The community feels the convenience in carrying out various transactions such as fund transfers, bill payments, and cash withdrawals. Furthermore, the majority of respondents expressed high levels of satisfaction due to the ease of access, speed of service, and proximity to bank branches. Therefore, BRILink services play a crucial role in expanding financial access and increasing public participation in the formal financial system in a sustainable manner.